2022
DOI: 10.3389/fimmu.2021.803475
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Neuroinfections, the Immune System and Neurological Disorders: A Focus on Africa

Abstract: Neurological disorders related to neuroinfections are highly prevalent in Sub-Saharan Africa (SSA), constituting a major cause of disability and economic burden for patients and society. These include epilepsy, dementia, motor neuron diseases, headache disorders, sleep disorders, and peripheral neuropathy. The highest prevalence of human immunodeficiency virus (HIV) is in SSA. Consequently, there is a high prevalence of neurological disorders associated with HIV infection such as HIV-associated neurocognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 287 publications
(423 reference statements)
0
14
0
1
Order By: Relevance
“…Viruses are abundant, ubiquitous in nature, and may be deleterious to human health. Prior viral infections, including Epstein-Barr virus (EBV) [1,2], Herpes Simplex virus (HSV) [3,4], Human immunodeficiency virus (HIV) [5,6], poliovirus [7,8], Zika virus [9,10], and many others have been associated with subsequent neurological damage [11]. Comorbidities and predisposing genetic risk factors for neurological and immunological dysfunction often vary among individuals in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses are abundant, ubiquitous in nature, and may be deleterious to human health. Prior viral infections, including Epstein-Barr virus (EBV) [1,2], Herpes Simplex virus (HSV) [3,4], Human immunodeficiency virus (HIV) [5,6], poliovirus [7,8], Zika virus [9,10], and many others have been associated with subsequent neurological damage [11]. Comorbidities and predisposing genetic risk factors for neurological and immunological dysfunction often vary among individuals in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…In Sub-Saharan Africa (SSA), secondary headache disorders caused by various infections are prevalent and contribute to a significant burden of disability and economic impact on patients and society (34). Sleep disorders, which are also prevalent in SSA, have been linked to infectious diseases such as human African trypanosomiasis and HIV (35).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Egypt identified meningitis as the second most common cause of secondary headache, following post-traumatic headache (35). In the Middle East and North Africa (MENA) region, other infectious diseases such as tuberculosis, HIV/AIDS, and brucellosis have also been associated with secondary headaches (34). In our current study, we investigated the frequency of headaches attributed to infections according to the ICHD-3 criteria (2).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is a need for proper research on various infections affecting the nervous system. Ngarka et al [5] study on neuroinfections in Africa demonstrated the need for a thorough investigation into the risk factors, triggering factors, and mechanisms underlying these infections. This would aid in the development of novel therapeutic approaches for the effective management of these infections [5] .…”
Section: Recommendationmentioning
confidence: 99%